Never look away [videorecording (DVD)] - Moth, Margaret Gipsy, 1951-2010; Amanpour, Christiane (Greenwich Entertainment, 2024)
"CNN camerawoman Margaret Moth fearlessly captures footage of war zones. After receiving catastrophic injuries in the crosshairs of battle, she returns to work with more courage than ever. An intimate portrait of a trailblazing female photojournalist. Features interviews with Moth's family and friends, including CNN's Christiane Amanpour. A Sundance film festival premiere directed by Lucy Lawless." --